AD, Volume 11, n° 4, 1986 - Full Issue - journal system, (Africa Development, 1986)
Table of Contents Introduction Thandika Mkandawire - Zenebeworke Tadesse ...................... i Development Theory and the Africa Predicament Peter P. Ekeh ............................ 1 Ebauche d'une Analyse de la Question Agraire en Ouganda Mahmood Mamdani ..................... 41 Women, Population and Food in Africa: The Zambian Case Mabel C. Milimo ....................... 95 Semiotic Constants and Perceptions of Change: A Study of the Symbolism and Imagery of Change and Development in African Literature Felix Mnthali .......................... 133 State and Society in Kenya: The Disintegration of the Nationalist Coalitions and the Rise of Presidential Authoritarianism, 1963-78 Peter Anyang' Nyong'o ....................... 175 The Crisis of International Migration in an Integrating West Africa: A Case Study of Nigeria and Ghana Yaa Frempomaa Yeboah ......................... 217 Books Received ........................... 257